PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR): STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BEI - Gustari, Rizki Asih; Kamaliah, Kamaliah; Afifah, Ulfa (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This research aims to examine the influence of profitability, company size, and ownership structure on Corporate Social Responsibility (CSR) disclosure. The research population includes non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) in 2020-2023, with 76 companies selected as samples using a purposive sampling approach. The approach applied in this research is a quantitative approach, with data analysis using panel data regression using Eviews 12 software. The results show that profitability has a negative effect on CSR disclosure, company size has a positive effect on CSR disclosure, institutional ownership has a negative effect on CSR disclosure, while public ownership does not show a significant effect on CSR disclosure